2014
DOI: 10.1016/j.janxdis.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of CBT outcome in older adults with GAD

Abstract: The current study is a secondary analysis of data from a randomized controlled trial of CBT for late-life GAD (Stanley et al., 2014) which provided an opportunity to examine predictors of outcome among those who received CBT. Participants were 150 older adults who were randomized to receive 10 sessions of CBT. Completer analyses found that homework completion, number of sessions attended, lower worry severity, lower depression severity, and recruitment site predicted 6-month worry outcome on the PSWQ-A, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 42 publications
(52 reference statements)
4
11
0
Order By: Relevance
“…Naturalistic and observational studies have found comorbid depression has no impact on outcomes (Kelly & Mezuk, 2017) or is associated with worse outcomes (Bruce et al, 2001). However, our findings are consistent with other interventional studies that found that psychiatric comorbidity (including depression) was associated with improved outcomes in persons receiving CBT and/or collaborative care (Kelly et al, 2015; Newman et al, 2010; Wetherell et al, 2005), but not all (Hundt et al, 2014). Differences may be due to variability in the assessment of depression.…”
Section: Discussionsupporting
confidence: 91%
“…Naturalistic and observational studies have found comorbid depression has no impact on outcomes (Kelly & Mezuk, 2017) or is associated with worse outcomes (Bruce et al, 2001). However, our findings are consistent with other interventional studies that found that psychiatric comorbidity (including depression) was associated with improved outcomes in persons receiving CBT and/or collaborative care (Kelly et al, 2015; Newman et al, 2010; Wetherell et al, 2005), but not all (Hundt et al, 2014). Differences may be due to variability in the assessment of depression.…”
Section: Discussionsupporting
confidence: 91%
“…In the treatment of depression with CBT, homework compliance has been correlated with significant clinical improvement and shown to predict decreases in both subjective and objective measures of depressive symptoms [ 17 - 23 ]. Similarly, homework compliance is correlated with short-term and long-term improvement of symptoms in anxiety disorders, including generalized anxiety disorder (GAD), social anxiety disorder (SAD), hoarding, panic disorder, and post-traumatic stress disorder (PTSD) [ 17 , 24 - 32 ]. Fewer studies have been done on homework compliance in other psychiatric conditions, but better homework compliance has been correlated with significant reductions in pathological behaviors in psychotic disorders [ 33 , 34 ], cocaine dependence [ 35 , 36 ], and smoking [ 37 ].…”
Section: Homework Non-compliance In Cbtmentioning
confidence: 99%
“…In this study, patients of the IG presented a statistically significant higher MMSE mean score than the ones of the CG. Even though patients of both groups present high scores (>27), by analysis of means, differences in the cognitive status can have an impact on the individual's ability to understand or to complete psychotherapeutic tasks (Hundt et al., ).…”
Section: Discussionmentioning
confidence: 99%